Digital video presentation in an EFL writing classroom / Yustinus Calvin Gai Mali - Mali, Yustinus Calvin Gai (Universiti Teknologi MARA Cawangan Kedah, 2018)
This qualitative study delved into students’ perspectives on the practices of a digital video presentation project in their English as a Foreign Language (EFL) writing class at an English Language Education Program of a private university in Central Java, Indonesia. Twenty-five students participated in this research by submitting their reflective journals that responded to five guiding questions. The study indicated some successes as well as challenges in the implementation aspects of the project. Implications for the integration of technology into EFL teaching and learning practices were also discussed in the paper.